The Effect of Animated Movie on The Students’ Procedural Writing at SMP Swasta Talitakum Medan - asmawati asmawati; desti karyawati gulo; Jernih ayu lestari sipahutar; siti syafiah; naomi bunga sari br.siboro (elt, 2019)
The objective of the study is to find out the significant effect of using Animated movie on students’ procedural writing achievement. In This research the writer used the experimental design. The population of this study was the seventh and eighth grade students of SMP Swasta Talitakum Medan and the 73 students of them were taken as the sample. The sample was obtained by random sampling technique. The data of the study were the students’ score in procedural writing. The data of the study were obtained by using essay tests which consist of 30 items. The data were analyzed by using t-test formula. The calculation showed that t-observed 2.07 by applying Animated Movie is higher than t-table (1.671) at the level significance (0.05) and df (71). Alternative hypothesis (Ha) is accepted. It means that teaching procedural writing by applying Animated movie affected the students’ procedural writing achievement.